Optimalisasi Peran dan Fungsi Baitul Maal Wat- Tamwil Dalam Menyalurkan Pembiayaan MUB Di Kota Surabaya - Faruk, Faruk; Fauziyah, Alvi; Majid Toyyibi, Abdul (El-kahfi | Jurnal Ekonomi Islam, 2024)
The purpose of this research is to find out the optimization of the role and function of BMT UGT Nusantara capem Sidodadi in channeling MSME financing in Sempir sub-district and also to find out how the financing mechanism for MUB (Barokah Business Capital) products is in this BMT. In this study the authors used a descriptive qualitative method. The author conducted interviews with the head of the BMT branch. AOSP BMT staff and also traders around BMT, and used financial reports owned by BMT and searched for literature related to research. With the research object of BMT UGT Nusantara Capem Sidodadi Surabaya. The results showed that BMT was not optimal in channeling financing due to a decrease in members applying for MUB financing every month, therefore BMT used a pick-up strategy where BMT went directly to the community and also related to the MUB financing mechanism carried out by BMT. by providing a number of requirements for members who apply for financing.